Treatment of male genital lymphedema: An integrated concept. Issue 2 (February 2015) - Torio-Padron, Nestor; Björn Stark, G.; Földi, Etelka; Simunovic, Filip
Summary Genital lymphedema is a debilitating condition. Currently, therapeutic concepts include conservative and surgical measures of genital volume reduction, but no therapy standards exist. The aim of this study was to analyze our experience with the treatment of male genital lymphedema and to describe our integrated concept, which combines perioperative complex decongestive physiotherapy (CDP) with surgical reduction. We conducted a retrospective study of 51 male patients who were treated in our clinic between 1998 and 2013, acquiring data on etiology, performed therapy, and complication rates. Forty-three (84%) of our patients suffered from primary and eight (16%) from secondary lymphedema. Two patients (4%) exhibited isolated penile affection and 22 (43%) isolated scrotal affection, while the majority (27 or 53%) exhibited penoscrotal lymphedema. All patients underwent inpatient CDP preceding and following surgery. Surgical therapy involved debulking the scrotum in 25 patients (49%), isolated penile reduction in two (4%), and penoscrotal reduction in 24 (47%). Hydrocoelectomy was performed in 22 (43%) patients. Following resection of the diseased tissue, the defects were closed primarily using adjacent healthy skin. There was no need for local flaps or skin grafts. Three patients suffered from complications requiring revision surgery: hematoma in two patients (4%) and wound dehiscence in one (2%). We measured the change in quality of life that was achieved by these procedures using the Glasgow Benefit Inventory questionnaire. The patients reported improvement in general functioning and physical health, whereas the social support score was largely unaffected by the procedure. Our results show that genital lymphedema patients can be reliably treated by combining conservative and surgical therapy. Prior conservative reduction of the genitals facilitates surgery and allows consistent results at a low complication rate, whereas surgical reduction serves to enhance and stabilize the results of conservative treatment.